Study of the Significance of Integrating Technology for Inquiry (NTeQ) Model in Undergraduate Teacher Education Programme - Ahuja, Amit (Indian Journal of Educational Technology, 2024)
Technology infusion in formal classroom teaching-learning supports the students in conceptual learning, retention and enrichment. Integrating Technology for Inquiry (NTeQ) model is a computer-based sequential learning innovation that integrates technology to promote inquiry-oriented, problem-solving or project-based learning. Present descriptive survey research was conducted to gauge the curricular implications of the NTeQ model and explore the attitude and learning experience of prospective teachers of undergraduate teacher education programs of teacher education institutions of GGSIP University, Delhi. Data analysis showed that in institutions, mere theoretical discussion on the NTeQ model and lack of interactive sessions in computer laboratories restricted the prospective teachers from retrieving the conceptual framework of the NTeQ model in the examination. This also led prospective teachers to develop a neutral attitude towards the NTeQ model as a learning tool. The teacher educators expressed the dire need for professional development programmes for themselves to explore the NTeQ model as a learning tool in formal classroom teaching-learning scenarios. The adequate technical infrastructure of teacher education institutions, simulation-based teaching practice through the NTeQ approach and incorporation of practical activities on the NTeQ model in the curriculum may promote the learning implications of the NTeQ model in classrooms. The study had educational implications for concerned stakeholders.